2006
DOI: 10.1007/s10531-005-0310-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Rodent Species Diversity and Abundance in a Kenyan Relict Tropical Rainforest

Abstract: Patterns of rodent species abundance and diversity were examined over a 5 months period in two areas of a Kenyan relict tropical rainforest. The two areas are subjected to different administrations which lead to various levels of anthropogenic disturbance: one can be considered relatively disturbed and one relatively undisturbed. Anthropogenic disturbance causes a reduction in woody stem density between 0 and 1.5 m and reduced understory tree canopy cover. Rodent abundance was estimated using the program CAPTU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The type of traps used and the great heterogeneity of habitats of the TNP (Adou Yao & N'Guessan, 2005) could justify this great diversity of terrestrial small mammals. Indeed, habitat heterogeneity is recognised as an important environmental parameter capable to influence the diversity and distribution of terrestrial small mammals on a given site (Caro, 2002;Magige & Senzota, 2006;Mortelliti & Boitani, 2006). This is due to the colonisation capacity of different habitats by terrestrial small mammals (Caro, 2001;Fitzherbert et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The type of traps used and the great heterogeneity of habitats of the TNP (Adou Yao & N'Guessan, 2005) could justify this great diversity of terrestrial small mammals. Indeed, habitat heterogeneity is recognised as an important environmental parameter capable to influence the diversity and distribution of terrestrial small mammals on a given site (Caro, 2002;Magige & Senzota, 2006;Mortelliti & Boitani, 2006). This is due to the colonisation capacity of different habitats by terrestrial small mammals (Caro, 2001;Fitzherbert et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This was in part explained by the abundance of shrubs, although the effect did not explain much variance in the model (Table 2). Presumably, shrubs offer shelter and food to rodents, the main predators, thereby increasing their abundance and activity (Simonetti 1989;Fedriani and Manzaneda 2005;Muñoz 2005;Mortelliti and Biotani 2006). Following this trend, the native forest (the least-degraded landscape unit) as well as shrubland showed heavy predation pressure (Fig.…”
Section: Landscape Unit Selectionmentioning
confidence: 97%
“…Trapping stations were then marked with unique codes written on ribbons for easy identification. Traps were hidden with dry leaf litter to protect them from rain and direct sunlight, and were set for three consecutive nights at each site per month, for 24 months from April 2020 through March 2022 and inspected once per day between 7:00 a.m. and 11:00 a.m. Mortelliti and Boitani (2006) and Musese et al (2023) have also found success in inspecting traps once a day, with no heat or cold deaths reported. The Capture- Mark Recapture (CMR) technique was used to capture rodents and each rodent captured was permanently marked with the unique number codes generated by the CMR software MARK as explained by Borremans et al (2015) .…”
Section: Methodsmentioning
confidence: 99%